MEMBANGUN MULTI KOMPETENSI PENDETA GBI (STUDI PENINGKATAN KUALITAS SUMBER DAYA PENDETA DI ERA POSTMODERN) - Ruben Yonathan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This research is motivated by the fundamental need to manage tasks and responsibilities in church ministry in the postmodern era, ensuring the availability of human resources with above-average multi-competencies. The rapid development of science and technology significantly impacts human life in various aspects. Specifically, we are currently facing the issue of Artificial Intelligence (AI). The method employed in this research is descriptive qualitative research. Findings from this research indicate that the postmodern era demands church leaders to possess multi-competencies. The presence of the postmodern era has altered the dynamics of social, cultural, and spiritual aspects of society. The biblical foundation is crucial in developing efforts for the Multi-Competence of Pastors in the Church of Bethel Indonesia to enhance the quality of resources as fitting leaders in the postmodern era. The conditions of society in the postmodern era are sporadic and dynamic, characterized by idealistic and individualistic traits, along with social life trending towards advancement, rationality, and even skepticism. Pastoral leadership also has a sustainability dimension, considering the holistic needs of individuals within the church and nation's communities. This research aims to build the multi-competence of Bethel Indonesia church pastors to have multi-competencies in this postmodern era.